People, profit and politics state-civil society relations in the context of globalization - Wui, Ma. Glenda Lopez; Tadem, Teresa S. Encarnacion (Third World Studies Center, College of Social Sciences and Philosophy, University of the Philippines, 2006)
"This research project on state-civil society relations in the context of globalization analyzes the relations between the Philippine state and selected civil-society actors in the context of globalization. It focuses on four sectors: the Benguet vegetable, hog, garment, and telecommunications industries. These sectors are widely known to have been affected by economic liberalization--negatively in the case of the first three, and positively in the case of the telecommunications industry. The project investigates two interrelated aspects of state-civil society relations: 1) how civil-society actors engage with official state agencies through various formal and informal strategies of dialogue, negotiation, and bargaining; and 2) the extent to which civil-society actors have been able to influence governmental policy making."--Introduction.